Clinical genetics: textbook for students of institutions of higher medical education, trained on the specialties "Internal Medicine", "Pediatrics", "Preventive Medicine" in the discipline "Medical Genetics" - Бочков, Н. П. медицинская генетика 19311019-20110928 Николай Павлович (Textbook, 2023)
All chapters of this textbook have been revised and enlarged in line with the development of medical science and practice. Chapters on multifactorial diseases, prevention, treatment of hereditary diseases, environmental genetics and pharmacogenetics have been updated substantially. The text is illustrated with diagrams and fi gures. The textbook presents new patterns of trends in genetics (epigenetics, small RNAs, uniparental disomies, genetic polymorphism, etc.), which were identifi ed in recent years. This edition is intended for students of institutions of higher medical education, trained on the specialties "Internal Medicine", "Pediatrics", "Preventive Medicine" in the discipline "Medical Genetics".